"A DIAMOND IS FOREVER" AND OTHER FAIRY TALES: THE RELATIONSHIP BETWEEN WEDDING EXPENSES AND MARRIAGE DURATION. (10th March 2015) - Francis‐Tan, Andrew; Mialon, Hugo M.
<x xml:space="preserve">Abstract</x> In this study, we evaluate the association between wedding spending and marriage duration using data from a survey of more than 3, 000 ever‐married persons in the United States. Controlling for a number of demographic and relationship characteristics, we find evidence that marriage duration is inversely associated with spending on the engagement ring and wedding ceremony. (JEL J12, Z1, D1)